2023
DOI: 10.3390/livers3020014
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria in Acetaminophen-Induced Liver Injury and Recovery: A Concise Review

Abstract: Mitochondria are critical organelles responsible for the maintenance of cellular energy homeostasis. Thus, their dysfunction can have severe consequences in cells responsible for energy-intensive metabolic function, such as hepatocytes. Extensive research over the last decades have identified compromised mitochondrial function as a central feature in the pathophysiology of liver injury induced by an acetaminophen (APAP) overdose, the most common cause of acute liver failure in the United States. While hepatocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 111 publications
0
7
0
Order By: Relevance
“…Male CD1 mice fasted overnight with only access to water ad libitum were dosed with either ApAP, or SRP-001 or vehicle (0.9% saline) (n = 5 for each treatment group) via PO dosing at concentrations of 600 mg/kg (for both ApAP and SRP-001) with an injection volume of 10 mL/kg body weight. We selected this dosage based on its well-documented characterization in previous research as an effective measure for evaluating ApAP-induced hepatotoxicity in preclinical rodent models 33 35 , 59 , 72 , 73 .…”
Section: Methodsmentioning
confidence: 99%
“…Male CD1 mice fasted overnight with only access to water ad libitum were dosed with either ApAP, or SRP-001 or vehicle (0.9% saline) (n = 5 for each treatment group) via PO dosing at concentrations of 600 mg/kg (for both ApAP and SRP-001) with an injection volume of 10 mL/kg body weight. We selected this dosage based on its well-documented characterization in previous research as an effective measure for evaluating ApAP-induced hepatotoxicity in preclinical rodent models 33 35 , 59 , 72 , 73 .…”
Section: Methodsmentioning
confidence: 99%
“…Hence, provided that glucuronidation and sulfation are active and hepatic glutathione stores are adequately maintained, therapeutic doses of APAP do not produce liver injury since all NAPQI generated is efficiently scavenged. However, the presence of preexisting conditions such as acute viral hepatitis, treatment with antitubercular drugs, or chronic alcoholism could cause liver injury even with therapeutic doses of APAP (8), though there are nuances to be considered in these scenarios (8).…”
Section: Drug Metabolism and Metabolic Activation Of Acetaminophen (A...mentioning
confidence: 99%
“…A relatively early change detected after exposure to an APAP overdose is an alteration in mitochondrial morphology to a donut-like topology in response to a decrease in mitochondrial membrane potential without compromised respiratory chain function (21). This is a reversible process once APAP is removed, and it has been reported that the donut topology maintains mitochondrial membrane potential and helps mitochondria resist autophagy (8). Thus, the second level of adaptation to formation of APAPprotein adducts once autophagic removal has been overwhelmed seems to be at the level of the mitochondria, which attempt to alter morphology and maintain respiratory function to tide over the functional deficits caused by mitochondrial protein adduct formation.…”
Section: Alterations In Mitochondrial Morphology Mitophagy and Mitoch...mentioning
confidence: 99%
“…Many experimental studies have shown that female mice are less susceptible to APAP hepatotoxicity than males and that the sex differences are substantial [17,18,35] . Many of the mechanisms have been elucidated by the Jaeschke group in Kansas [18,36,37] .…”
Section: Sex Differences In the Toxicity Of Acetaminophenmentioning
confidence: 99%